Meromorphic mappings of torus onto the Riemann sphere - Khrystiyanyn, A.Ya.; Kondratyuk, A.A. (Carpathian Mathematical Publications, 2012)
The meromorphic mappings of the two dimensional torus onto the Riemann sphere are studied. Their connections with loxodromic meromorphic functions in the punctured plane are considered.